STUDENTS’ PERCEPTION AND SATISFACTORY LEVEL FOR PREPARATION OF PORCELAIN FUSED TO METAL CROWN IN PRECLINICAL FIXED PROSTHODONTICS: PERSEPSI DAN TINGKAT KEPUASAN MAHASISWA TERHADAP PREPARASI MAHKOTA PORSELIN DI PREKLINIK PROSTODONTI CEKAT - Marlynda Ahmad; Natasya Ahmad Tarib (TALENTA, 2010)
Preclinical session is one way of training dental undergraduates to prepare teeth for restorations. The aims of the study were to evaluate students’ perception and satisfactory level in preparing tooth for porcelain fused to metal crown in preclinical fixed prosthodontics sessions. A total of 104 fourth year dental undergraduates students participated in this study. Lecture consisted of the diagrams of step-by-step procedure in preparing porcelain fused to metal crown on tooth 24. Video demonstration was also conducted. After they were satisfied with the preparation, they were asked to answer a series of multiple choice questions on their performance. Only 92 students completed the questionnaire. Majority of the students taught that their occlusal and axial reductions were about right. As for the margin, 50 students claimed that the margin was located on gingival margin while 88 students said that they prepared shoulder margin buccally and 4 students created chamfer margin buccally. Seventy four out of 92 students were slightly satisfied with their crown preparations. Twenty five students said that they were very competent and confident in doing crown preparation to patients. Almost all fourth year dental students could perform porcelain-fused-to-metal crown preparation with confidence. As conclusion, exposure to our teaching methods and aids appears to help them in preparing these tasks.